Matter and Methods at Low Temperatures - Pobell, Frank (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Matter and Methods at Low Temperatures contains a wealth of information essential for successful experiments at low temperatures, which makes it suitable as a reference and textbook. The first chapters describe the low-temperature properties of liquid and solid matter, including liquid helium. The major part of the book is devoted to refrigeration techniques and the physics on which they rely, the definition of temperature, thermometry, and a variety of design and construction techniques. The lively style and practical basis of this text make it easy to read and particularly useful to anyone beginning research in low-temperature physics. Low-temperature scientists will find it of great value due to its extensive compilation of materials data and relevant new results on refrigeration, thermometry, and materials properties. Problems are included as well. Furthermore, this third edition also describes newly developed low-temperature experimentation techniques and new materials properties; it also contains many additional references and a list of suppliers of cryogenic equipment.